Tipologi Karya Ulama Pesantren di Kediri Jawa Timur - Kartini SI, Retno (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2014)
This article is the result of research on the inventory work of scholars in boarding school in Kediri, East Java. The collected works of scholars from seven Islamic boarding inventoried in Kediri. In the seven Islamic boarding schools found 281 works of scholars. The works are written in a variety of forms ranging from original writing, translation, khulasah or Mukhtasar, and commentary. Most of the work of scholars are used as teaching materials at the school and is also used by the general public. Given the work of these scholars ever and is still used up to now, the effect also varied, ranging in scope of global, national, regional, and local. All 281 books and books by scholars in Kediri, when viewed from the Islamic texts describe rahmatan lil a'lamin. Islamic teachings set forth in the various papers that describe Islam a peaceful, tolerant, and loaded with multiculturalism.Keywords: Typology, The work of Ulama, school, Kediri